Neo-BCV: A Novel Bacterial Liquid Complex Vaccine for Enhancing Dendritic Cell-Mediated Immune Responses Against Lung Cancer - Zilong Zhu; Zhuze Chu; Fei Fei; Chenxi Wu; Zhengyue Fei; Yuxia Sun; Yun Chen; Peihua Lu (Vaccines)
Background: In the past decade, immunotherapy has become a major choice for the treatment of lung cancer, yet its therapeutic efficacy is still relatively limited due to the various immune escape mechanisms of tumors. Based on this, we introduce Neo-BCV, a novel bacterial composite vaccine designed to enhance immune responses against lung cancer. Methods: We investigated the immune enhancing effect of Neo-BCV through in vivo and in vitro experiments, including flow cytometry, RNA-seq, and Western blot. Results: We have demonstrated that Neo-BCV can promote Dendritic cells (DCs) maturation and induce DCs differentiation into pro-inflammatory subgroups, significantly enhancing cytotoxic T lymphocyte (CTL)-mediated anti-tumor responses. Transcriptome sequencing revealed that Neo-BCV exerts its effects by specifically inhibiting the JAK2-STAT3 signaling pathway, a crucial regulator of cancer progression, metabolism, and inflammation. Moreover, Neo-BCV significantly improved the immune microenvironment in both tumor and spleen tissues without inducing notable toxic effects in major organs. Conclusions: These findings highlight Neo-BCV’s potential as a safe and effective therapeutic strategy, offering a novel avenue for clinical translation in lung cancer immunotherapy.